Changes in the dopaminergic circuitry and adult neurogenesis linked to reinforcement learning in corvids - Parishar, Pooja; Rajagopalan, Madhumita; Iyengar, Soumya (Frontiers in Neuroscience, 2024)
The caudolateral nidopallium (NCL, an analog of the prefrontal cortex) is known to be involved in learning, memory, and discrimination in corvids (a songbird), whereas the involvement of other brain regions in these phenomena is not well explored. We used house crows (Corvus splendens) to explore the neural correlates of learning and decision-making by initially training them on a shape discrimination task followed by immunohistochemistry to study the immediate early gene expression (Arc), a dopaminoceptive neuronal marker (DARPP-32, Dopamine- and cAMP-regulated phosphoprotein, Mr 32 kDa) to understand the involvement of the reward pathway and an immature neuronal marker (DCX, doublecortin) to detect learning-induced changes in adult neurogenesis. We performed neuronal counts and neuronal tracing, followed by morphometric analyses. Our present results have demonstrated that besides NCL, other parts of the caudal nidopallium (NC), avian basal ganglia, and intriguingly, vocal control regions in house crows are involved in visual discrimination. We have also found that training on the visual discrimination task can be correlated with neurite pruning in mature dopaminoceptive neurons and immature DCX-positive neurons in the NC of house crows. Furthermore, there is an increase in the incorporation of new neurons throughout NC and the medial striatum which can also be linked to learning. For the first time, our results demonstrate that a combination of structural changes in mature and immature neurons and adult neurogenesis are linked to learning in corvids.